Study of double windows efficiency in order to improve sound insulation in buildings - Oliveira, Marco Aurélio (2016)
The aim of this research is to evaluate sound insulation behavior of double windows, when windows, when a second window is placed upon a previous one, keeping an air layer between them. This was done through standard tests carried out at the insulation chamber of the Acoustics Laboratory of Federal University of Santa Maria in accordance with international norms ISO 10140-2 and ISO 717-1. First, low air hermetic windows were duplicated, each one having Rw = 18 dB. Second, good air hermetic windows were duplicated. The objective, through this technique, was to find out sound insulation improvement of double windows under the two mentioned circumstances. It was verified that low air hermetic double window obtained Rw = 26 dB, with an increase of 8 dB in relation to just one window of the same typology. In relation to good air hermetic double window, a Rw final of 37 dB was obtained, considering that the increase in sound insulation depends on the initial performance of the first installed window. The gain in insulation in the second instance was between 4 to 8 dB, mainly in relation to low and medium frequencies. Therefore, it was possible to quantify which sound insulation improvement could be done on faÃ§ades employing the technique of double windows in order to contribute to the improvement and quality of buildings in Brazil.